MENINGKATKAN RASA TANGGUNG JAWAB SISWA DALAM BELAJAR SECARA KELOMPOK MELALUI METODE KUIS TIM - Tanti Setiana (Pusat Studi Pendidikan dan Kreativitas Guru, 2021)
There are various learning problems faced by teachers in schools, including the problem of decreasing student responsibility in completing their learning tasks. Responding to this certainly requires serious efforts to solve this problem immediately. To solve this problem of decreasing responsibility, students must use certain strategies or methods and approaches. Methods that are considered very appropriate, one of which is the active learning method of the team quiz. With the Team Quiz method, it is hoped that the responsibility of students in the study group can increase.